Juridical Analysis Law Enforcement Of The Crime Of Theft By Minors To Realize Legal Certainty: Research Studies at Tanjung Pinang Resort Police - Christhopher Theodore Nathanael; Darwis Anatami; Ramon Nofrial; Soerya Respationo; Erniyanti Erniyanti (International Journal of Social Science and Humanity, 2024)
Children are a mandate and a gift from God Almighty who has inherent dignity and worth as a whole human being and at the same time is the heir and shaper of the nation's future. The research method used is the Normative Juridical method with an Empirical Sociological approach. By using Primary and Secondary Data through interviews and observations. A part from that, the author uses secondary data through the library. As an analytical tool the author uses Grand Theory (Law enforcement theory) Middle Theory (Legal System Theory) and Applied Theory (Relative theory) This study aims to find out the legal arrangements for the crime of theft by minors to realize Legal certainty, to find out the implementation of law enforcement for the crime of theft by minors to realize Legal certainty and to find out the obstacles/obstacles and solutions in law enforcement of theft by minors to realize legal certainty. Legal Arrangements for the Crime of Theft by Children to Achieve Legal Certainty, Research Studies at Tanjung Pinang Resort Police are in accordance with the prevailing laws and regulations. Implementation of Law Enforcement for the Crime of Theft by Children To Realize Legal Certainty, Research Studies at the Tanjungpinang Resort Police have been going well but in fact, children are still found in the field who commit the Crime of Theft every year, it has increased, especially in the Tanjung Pinang, Archipelago, this is seen from the level of law enforcement factors against children who are in conflict with the law in Tanjung Pinang, for this reason, the performance of the TanjungPinang Police is needed to prevent the crime of theft committed by children